2010
DOI: 10.1002/clc.20720
|View full text |Cite
|
Sign up to set email alerts
|

Primary Percutaneous Coronary Interventions in Nonagenarians

Abstract: Background:The optimal treatment of very elderly patients with ST elevation myocardial infarction (STEMI) is not yet defined. The aim of this study is to present the feasibility and safety of primary percutaneous coronary interventions (PCI) in nonagenarians.Methods:A retrospective analysis of all patients who underwent primary PCI due to STEMI between 2004 and 2008 was performed. Patients age 90 years or older at the time of the procedure were identified and studied.Results:Twenty‐two patients fulfilled the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…This is similar to the outcomes of PCI in octogenarians in the ACC-NCDR, where the mortality rate was nearly 14% in those who presented with an acute MI within 24 hours, and less than the 27% observed in-hospital mortality in nonagenarians in a retrospective analysis. 15,28 Despite the high mortality rate observed in this patient group, it is much less than those patients treated medically for STEMI or cardiogenic shock. 29 Although in our registry, the STEMI and cardiogenic shock populations had the highest rate of mortality and other procedure-related complications, we feel that this risk is appropriate given the morbidity and mortality associated with medical therapy alone.…”
Section: Discussionmentioning
confidence: 94%
“…This is similar to the outcomes of PCI in octogenarians in the ACC-NCDR, where the mortality rate was nearly 14% in those who presented with an acute MI within 24 hours, and less than the 27% observed in-hospital mortality in nonagenarians in a retrospective analysis. 15,28 Despite the high mortality rate observed in this patient group, it is much less than those patients treated medically for STEMI or cardiogenic shock. 29 Although in our registry, the STEMI and cardiogenic shock populations had the highest rate of mortality and other procedure-related complications, we feel that this risk is appropriate given the morbidity and mortality associated with medical therapy alone.…”
Section: Discussionmentioning
confidence: 94%
“…Previous multivariate logistic regression analyses in the literature revealed independent risk factors of in-hospital death for very old patients: cardiogenic shock, myocardial infarction without shock, left ventricular ejection fraction < 35%, renal insufficiency, age > 85 years and diabetes mellitus [10],[17],[21],[22]. As approximately 85% of the nonagenarians in our series had one or more indicators of clinical instability or worse prognosis (acute MI, cardiogenic shock, diabetes), we found an in-hospital mortality rate of 13%.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] Several studies demonstrated a continuous, curvilinear manner of mortality after elective coronary angiography and/or coronary intervention with increasing age, ranging from about 0.5% for patients < 55 years old to about 5% for patients > 85 years old. 7) This difference may be even more pronounced in the setting of acute coronary syndrome.…”
Section: )mentioning
confidence: 99%